2021
DOI: 10.1039/d0ra09095f
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining an immunoaffinity monolithic material: poly(GMA-co-EDMA) functionalized with an HPV-derived peptide using a thiol–maleimide reaction

Abstract: In this investigation, an organic monolithic material of poly(GMA-co-EDMA) was functionalized with a peptide via Michael addition chemistry for isolating and pre-concentrating antibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 32 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…As mentioned above, the high reactivity of maleimides is caused by their behavior as an electrophile, due to the α,β-unsaturation and the presence of two carbonyl groups, which allows them to react quickly with nucleophiles such as thiolate groups, obtaining Considering the great applicability and versatility of this reaction, and its relevance to the field of biochemistry and particularly the construction of conjugate systems, we used this reaction to join the 6-maleimidehexanoic acid to a peptide which contained a N-terminal cysteine. This reaction was monitored via RP-HPLC, and it was observed that the chromatographic profile presented two signals corresponded to addition reaction products [14]. In this context, the thiol-maleimide addition was studied in the present investigation, using as a model the reaction between L-Cysteine (Cys) and 6-maleimide hexanoic acid (Mhx) under different experimental conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned above, the high reactivity of maleimides is caused by their behavior as an electrophile, due to the α,β-unsaturation and the presence of two carbonyl groups, which allows them to react quickly with nucleophiles such as thiolate groups, obtaining Considering the great applicability and versatility of this reaction, and its relevance to the field of biochemistry and particularly the construction of conjugate systems, we used this reaction to join the 6-maleimidehexanoic acid to a peptide which contained a N-terminal cysteine. This reaction was monitored via RP-HPLC, and it was observed that the chromatographic profile presented two signals corresponded to addition reaction products [14]. In this context, the thiol-maleimide addition was studied in the present investigation, using as a model the reaction between L-Cysteine (Cys) and 6-maleimide hexanoic acid (Mhx) under different experimental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The use of this click reaction can be found in various examples, including: (i) Incorporation of peptide motifs that allow the construction of antibody-drug conjugates (ADCs) [6,7]; (ii) Coupling of Pt(IV) coordination compounds with maleimide and linear peptide molecules [8,9]; (iii) Design and synthesis of nanoparticles such as molecular cages or nanoparticle drug delivery systems [10,11]; (iv) Construction of dendrimeric molecules [12]; (v) Obtaining oligonucleotides-peptide [13]; (vi) Functionalization of a monolithic organic support, poly(GMA-co-EDMA), with a maleimide hexanoic (Mhx) group that allows the incorporation of a peptide containing a residue of cysteine at the N-terminal, a reaction that was found to be selective under mild conditions [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, poly(GMA-co-EDMA) was utilized to enhance the detection limit of the μPAD, forming the novel sPAD. It was reported that poly(GMA-co-EDMA) is capable of covalently binding with carboxyl groups, 39 therefore, this mechanism was applied to immobilize biomolecules covalently to the proposed sPAD. The synthesis of the monolith layer began with the addition of the GMA and EDMA mixture to the surface of cellulose paper.…”
Section: Resultsmentioning
confidence: 99%
“…Human papillomaviruses (HPV) are the causative agents of cervical, anal, and vaginal cancers to name a few. The human papillomavirus L1 protein (HPV-L1) is found in 90% of the HPV capsid and is known to be directly involved in the process of the HPV infection of host cells . These viruses are grouped as low-risk or high-risk depending on the type of lesion they cause.…”
mentioning
confidence: 99%